Is there a place for ultrasound in diagnosing sarcopenia? - Rondaij Tadej; Kozjek Nada Rotovnik; Jerele Cene; Jordan Taja (Radiology and Oncology)
Sarcopenia is a progressive and generalised skeletal muscle disorder which presents as loss of muscle mass and function and is associated with increased likelihood of adverse outcomes, reduced quality of life and increased mortality. In developed countries, the prevalence of sarcopenia is rising due to increasing life expectancy. Still, in many clinical settings, sarcopenia may be overlooked and undertreated. While several tools are available for assessment of muscle mass and quality, there remains a need for safe, reliable and accurate diagnostic methods which can be implemented for both sarcopenia diagnosis and the evaluation of treatment efficacy.